THE ORIGINS OF DEMOCRACY AS AN ESSENTIAL FACTOR OF STABILIZATION OF THE DEMOCRATIC REGIMES - Романюк, О.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The fundamental idea of this article is in the substation of the thesis: the origins of the democratic regimes essentially  influence the process of its stabilization. The author distinguishes two types of the democracies: original and imitational, according to their origins. The potential threats of imitational democracy highlighted in this article. The author makes following conclusions: news democratic regimes must not blindly copy the institutes and standards of stable democracies; the process of transit from electoral to liberal democracy requires neutralization the threats of democratic development; to be saved the democracy must have defensive capacity.